A REVIEW OF SEPTIC INDUCED ABORTION CASES IN ONE YEAR AT KHYBER TEACHING HOSPITAL,PESHAWAR - Naib, Jamila M.; Siddiqui, Muhammad Ilyas; Afridi, Bilqis (Journal of Ayub Medical College Abbottabad, 2004)
Background: Working in a tertiary level hospital we get complicated cases as a result of termination or attempts at termination of unwanted pregnancies. Most of the patients that we get are complicated and need expensive treatments including surgery. This study was conducted to assess the out come of septic induced abortion cases in a year. Methods: It was conducted at the Department of Obstetrics and Gynaecology, unit B, Khyber Teaching Hospital, Peshawar, from 1.7.01 to 30.6.02. The data of a total of 28 patients admitted as emergency cases with septic induced abortion in above period were collected. History, management given, post operative care, complications and associated morbidity and mortality were taken into account and result compiled. Results: 78.5% patients with unsafe abortions were multi gravida. Termination was attempted at home or other small centers. 57% had history of surgical interference, 28.5% had used a mechanical device. 78.5% patients needed evacuation and curettage, 42% had laparotomy for visceral injuries. 15% patients had a subtotal hysterectomy. 57% patients had associated complications. 7.5% patients who came with septicemic shock died. Conclusion: Septic induced abortion is an important contributor to maternal morbidity and mortality, increasing the burden on not only the patients but health workers and their resources. However, it is preventable, and we suggest commitment to health education, family planning promotion and bringing down the rates of unsafe abortions as solutions to the problems. Key words: Septic induced abortion, Methods of termination, Complications, Outcome.